“The most relaxing song in the world”? A comparative study - Shepherd, Daniel; Hautus, Michael J; Giang, Edmund; Landon, Jason (Psychology of music, 2023)
The objectives of the current study were to obtain four physiological measures sensitive to stress and compare the nature of their decline after a stress task while listening to different sounds. Particular focus was placed on examining the ability of the song “Weightless”, which has been heralded as “the most relaxing song in the world,” to reduce acute stress as measured physiologically. A single-subjects design was deployed with 57 university students acting as participants. Outcome measures were skin conductance, heart rate, respiration rate, and respiration depth that were obtained during a 4-min rest period containing the sound conditions (silence, monaural beats [6 and 16 Hz], aircraft noise,“Weightless”) and referenced to a proceeding stress task. “Weightless” and the 6-Hz monaural beat had significantly lower mean skin conductance than the reference condition (silence), but no differences were noted for rate of decline or final asymptote. Furthermore, after 4 min, “Weightless” was associated with a 36.09% decrease in skin conductance level, favorable to that reported by the song’s creators. In terms of heart rate decline, “Weightless” was no more effective than any other of the sound conditions, while for respiration rate, it was significantly less effective than silence and the 6-Hz monaural beat. Overall, there was evidence that the song “Weightless” was an effective tool to reduce acute stress.